Cytokine production by CD4+ T cells specific for coagulation factor VIII in healthy subjects and haemophilia A patients - Hu, Genlin; Guo, Delan; Key, Nigel S.; Conti-Fine, Bianca M. (Thrombosis and Haemostasis, 2007)
HaemophiliaA patients treated with human factorVIII (fVIII) may develop antibody (Ab) inhibitors to fVIII. FVIII-specific CD4+ T cells are common in haemophilia A patients, but also in healthy subjects who do not have a sustained anti-fVIII Ab response. Here, we examined the fVIII-induced IFNγ -, IL-4- and TGF- β 1-producing CD4+ T blasts by culturing peripheral blood mononuclear cells (PBMC) from controls and patients with recombinant fVIII. FVIII exposure significantly increased IFNγ - and IL-4-, but not TGF-β 1-producing CD4+ T blasts in patients with inhibitors. Patients without inhibitors had fVIII-induced IFNγ - andTGF-β 1-,but not IL-4-producing CD4+ T blasts.Controls did not have IL-4-producing CD4+ T blasts. However, controls whose PMBC proliferated in response to fVIII had fVIII-induced CD4+ T blasts that produced IFN-γ, the number of which correlated with the intensity of the proliferative response to fVIII of their PMBC, whereas controls whose PMBC did not proliferate to fVIII had predominantly fVIII-induced CD4+ T blasts that producedTGF- β 1.The presence in controls and patients without inhibitors of fVIII-induced IFN-γ -producing CD4 + T cells, but not IL-4-producing CD4+ T cells, which are abundant in inhibitor patients, suggests a role of Th1 cells in initiating the immune response to fVIII, and of Th2 cells in the development of strong inhibitor production. The polarized high ratios of Th3/Th1 and Th3/Th2 in controls and patients without inhibitors suggest that a preponderance ofTh3 cells in the response to fVIII may help to maintain tolerance to fVIII.
Keywords: CD4+ T cells; cytokines; factor VIII; hemophilia A; inhibitors